Effect of GaN-Based Distributed Bragg Reflector on Optical Properties of CH3NH3PbBr3 Crystals - Feng Jiang; Yiwei Duan; Jiawen Song; Zhe Luo (Energies, 2023)
As a photoelectric material, the luminescent efficiency improvement of organic–inorganic perovskite material is a hot topic. This work fabricated a nanoporous distributed Bragg reflector based on GaN with a periodic structure using electrochemical etching methods. Considering the fact that hybrid perovskite materials are difficult to prepare on an inorganic GaN-based substrate, ultraviolet ozone treatment was implemented to enhance the surface activity of the prepared distributed Bragg reflector substrate. Cubic CH3NH3PbBr3 crystals with smooth surfaces and precise edges were successfully prepared on the ozone-treated distributed Bragg reflector substrate by a two-step immersion method in the air environment. The structural property of the prepared CH3NH3PbBr3 crystals was investigated using X-ray diffraction, scanning electron microscopy and Fourier-transform infrared spectroscopy. The structural analysis results showed that CH3NH3PbBr3 crystals grown on the prepared distributed Bragg reflector and reference substrates have the same structure, with a good crystal quality. The photoluminescence intensity of CH3NH3PbBr3 crystals grown on the distributed Bragg reflector was significantly enhanced. The enhancement is approximately 3.11-fold compared with CH3NH3PbBr3 crystals grown on the unetched reference GaN substrate. Moreover, there is a 7.2 nm spectral blue shift. The enhancement of the photoluminescence intensity could be attributed to the out-coupling of emission light in the prepared crystals, and the blue shift could be attributed to the stress relaxation caused by the nanoporous GaN structure of the distributed Bragg reflector substrate.